Perovskite battery and preparation method thereof

By modifying the electron transport layer and hole transport layer of perovskite batteries, the problem of insufficient carrier transport capability at the interface of perovskite batteries is solved, and the photoelectric conversion efficiency and stability are improved. Effect.

CN119451384AActive Publication Date: 2025-02-14INNER MONGOLIA ERDOS ELECTRIC POWER & METALLURGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411264558.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-02-14
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Existing perovskite batteries have challenges in improving interfacial carrier transmission capabilities, especially defects in buried interfaces and perovskite/HTL interfaces affect device performance.

Method used

By modifying the electron transport layer and the hole transport layer using humic acid compounds, the modified electron transport layer and the hole transport layer are formed, thereby improving the interface performance of the perovskite battery.

Benefits of technology

The modified perovskite battery shows improved photoelectric conversion efficiency and stability, effectively improving the performance of perovskite devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451384A_ABST
    Figure CN119451384A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite cells, and provides a perovskite cell and a preparation method thereof.The perovskite cell comprises an electron transport layer and a hole transport layer, the electron transport layer comprises an electron transport layer main material modified by a humic acid compound, and the hole transport layer comprises a hole transport layer main material modified by a humic acid compound. The hole transport layer comprises a hole transport layer main body material modified by a humic acid compound. The preparation method comprises the following steps: preparing a humic acid compound modified electron transport layer on a transparent conductive oxide substrate, then carrying out ozone wetting treatment, then coating a perovskite absorption layer, then spin-coating a humic acid compound modified hole transport layer, and finally evaporating an electrode to carry out a subsequent assembly process of a complete cell. And the high-performance perovskite battery is obtained. The method for preparing the perovskite cell provided by the invention is low in raw material cost and simple in modification process, and the prepared perovskite cell can effectively improve the photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite batteries, and in particular relates to a perovskite battery and a preparation method thereof. Background Art

[0002] In perovskite solar cells, the rapid transport and efficient separation of photogenerated carriers are necessary conditions for obtaining high-performance photovoltaic devices. Photovoltaic efficiency depends largely on the interface between perovskite and the electron transport layer (ETL), as well as the interface between perovskite and the hole transport layer (HTL). Therefore, interface passivation is a long-lasting hot topic. After rapid development in recent years, the efficiency of perovskite solar cells has increased from 3.8% first reported in 2009 to 26%, which is comparable to crystalline silicon solar cells, and has also made significant progress in stability.

[0003] One of the important strategies to improve the efficiency of perovskite cells is to improve the carrier transport capacity between interfaces; among them, interface passivation engineering is a feasible and effective method to reduce the interface defects, interface residual stress and interface non-radiative recombination caused by interface energy level mismatch at the interface between the light absorption layer and the electron / hole transport layer. It can effectively improve the mobility of carriers and have a decisive influence on the performance of the device. For positive structure perovskite solar cells, it has been proven that the energy level structure of the top interface of the device can be effectively regulated by constructing a two-dimensional / three-dimensional heterostructure on the surface of the perovskite film, thereby improving the separation and subsequent transport efficiency of photogenerated carriers. However, since the interface modification material is easily destroyed by the subsequent perovskite film preparation process, the passivation modification of the buried interface of the device (the lower interface, i.e., the interface of the perovskite light absorption layer / electron transport layer) is still in the development stage. In addition, in the positive structure battery device, compared with other similar materials, SnO2 has unique advantages such as low-temperature preparation and high electron transport capacity, which has always been highly valued by the research community, but the deep energy level defects derived from the low-temperature synthesis environment greatly damage the nucleation and crystallization quality of the perovskite film. Meanwhile, the perovskite / HTL interface is also prone to defect formation. Common HTL contacts have strong non-radiative recombination losses and hinder the extraction of interfacial carriers due to the large energy barrier.

[0004] Therefore, there is an urgent need for a perovskite cell and a preparation process thereof that can improve the efficiency of perovskite devices. Summary of the invention

[0005] The purpose of the present invention is to provide a high-performance perovskite battery prepared by humic acid double interface modification and a preparation method thereof. This preparation method utilizes humic acid materials with abundant sources and low cost as raw materials to simultaneously modify the perovskite / ETL interface and the perovskite / HTL interface of the perovskite battery device, thereby improving the efficiency and stability of the perovskite device.

[0006] To achieve the above-mentioned purpose of the invention, the technical solution of the present invention is as follows:

[0007] According to a first aspect of the present invention, a perovskite battery is provided, comprising an electron transport layer and a hole transport layer, wherein the electron transport layer comprises an electron transport layer main material modified by a humic acid compound, and the hole transport layer comprises a hole transport layer main material modified by a humic acid compound.

[0008] In one aspect of the present invention, the electron transport layer is obtained by solidifying a modified electron transport layer main material solution, and the modified electron transport layer main material solution is obtained by the following steps:

[0009] providing a solution containing an electron transport layer host material;

[0010] The solution containing the electron transport layer main material is doped and modified by using a humic acid compound to obtain a modified electron transport layer main material solution.

[0011] In one aspect of the present invention, the hole transport layer is obtained by solidifying a modified hole transport layer main material solution, and the modified hole transport layer main material solution is obtained by the following steps:

[0012] providing a solution comprising a hole transport layer host material;

[0013] The solution containing the hole transport layer main material is modified by using the humic acid compound to obtain a modified hole transport layer main material solution.

[0014] In one aspect of the present invention, the humic acid compound can be selected from at least one of humic acid, humate, fulvic acid, humic acid ester, humic acid aldehyde, humic acid amide and humic acid.

[0015] The humate may be a metal humate such as a sodium humate or a calcium humate, or a non-metal humate such as an ammonium humate or an organic ammonium humate.

[0016] As an example of the present invention, the humic acid compound is humic acid.

[0017] As an example of the present invention, the humic acid compound is a humate, specifically sodium humate.

[0018] In one aspect of the present invention, in the modified electron transport layer host material solution, the concentration of the humic acid compound is selected from 0.001-2 mg / mL.

[0019] As an example of the present invention, in the modified electron transport layer main material solution, the concentration of the humic acid compound is 0.2 mg / mL.

[0020] In one aspect of the present invention, in the modified hole transport layer host material solution, the concentration of the humic acid compound is selected from 0.001-5 mg / mL.

[0021] As an example of the present invention, in the modified hole transport layer main material solution, the concentration of the humic acid compound is 0.5 mg / mL.

[0022] In one aspect of the present invention, the host material of the hole transport layer is selected from any one of NiOx, 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) and tri(4-iodophenyl)amine.

[0023] In one aspect of the present invention, the electron transport layer host material is selected from SnO2.

[0024] According to a second aspect of the present invention, a method for preparing the above-mentioned perovskite cell is provided, wherein the perovskite cell has an upright structure, and is provided with a transparent conductive oxide substrate, an electron transport layer, a perovskite absorption layer, a hole transport layer and a metal electrode in sequence from bottom to top; the method comprises the following steps:

[0025] Step 1-1: preparing an electron transport layer main material solution modified by a humic acid compound and coating the modified electron transport layer main material solution on the transparent conductive oxide substrate, and obtaining an electron transport layer after curing;

[0026] Step 2-1: coating a perovskite absorption layer on the electron transport layer to form a perovskite absorption layer;

[0027] Step 3-1: coating a hole transport layer main material solution modified by a humic acid compound on a surface of the perovskite absorption layer away from the electron transport layer, and obtaining a hole transport layer after curing;

[0028] Step 4-1: Perform the process of evaporating electrodes and, after subsequent assembly steps, obtain a perovskite cell with an upright structure.

[0029] In one aspect of the present invention, between step 1-1 and step 2-1, a process of subjecting the electron transport layer to ozone wettability treatment is also included, wherein the ozone wettability treatment is to place the electron transport layer in an ozone cleaning machine and perform surface ozone cleaning, and the cleaning time is selected from 15-30 minutes.

[0030] In one aspect of the present invention, in step 1-1, the coating method is selected from spin coating, blade coating, spray coating or drop coating.

[0031] In one aspect of the present invention, in step 3-1, the curing method is low temperature calcination annealing at 150°C-180°C.

[0032] In one aspect of the present invention, in the step of preparing a perovskite cell with a normal structure, in the modified electron transport layer host material solution, the concentration of the humic acid compound is selected from 0.001-2 mg / mL.

[0033] As an example of the present invention, in the modified electron transport layer main material solution, the concentration of the humic acid compound is 0.2 mg / mL.

[0034] In one aspect of the present invention, in the step of preparing a perovskite cell with a normal structure, in the modified hole transport layer host material, the concentration of the humic acid compound is selected from 0.001-5 mg / mL.

[0035] As an example of the present invention, in the modified hole transport layer main material solution, the concentration of the humic acid compound is 0.5 mg / mL.

[0036] In one aspect of the present invention, in the step of preparing a perovskite cell having a normal structure, the main material of the hole transport layer is selected from any one of NiOx, 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene and tri(4-iodophenyl)amine.

[0037] In one aspect of the present invention, in the step of preparing a perovskite cell having a normal structure, the electron transport layer host material is selected from SnO2.

[0038] According to a third aspect of the present invention, a method for preparing the above-mentioned perovskite cell is provided, wherein the perovskite cell has an inverted structure, and is provided with a transparent conductive oxide substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and a metal electrode in sequence from bottom to top. The method comprises the following steps:

[0039] Step 1-2: preparing a hole transport layer main material solution modified by a humic acid compound and coating the modified hole transport layer main material solution on the transparent conductive oxide substrate, and obtaining a hole transport layer after curing;

[0040] Step 2-2: coating a perovskite absorption layer on the hole transport layer to form a perovskite absorption layer;

[0041] Step 3-2: coating a solution of a main material of an electron transport layer modified by a humic acid compound on a surface of the perovskite absorption layer away from the hole transport layer, and obtaining an electron transport layer after curing;

[0042] Step 4-2: Perform the process of evaporating electrodes and, after subsequent assembly steps, obtain a perovskite cell with an inverted structure.

[0043] In one aspect of the present invention, in step 1-2, the coating method is selected from spin coating, blade coating, spray coating or drop coating.

[0044] In one aspect of the present invention, in the step of preparing a perovskite cell with an inverted structure, in the modified electron transport layer host material solution, the concentration of the humic acid compound is selected from 0.001-2 mg / mL.

[0045] As an example of the present invention, in the modified electron transport layer main material solution, the concentration of the humic acid compound is 0.2 mg / mL.

[0046] In one aspect of the present invention, in the step of preparing a perovskite cell with an inverted structure, in the modified hole transport layer host material, the concentration of the humic acid compound is selected from 0.001-5 mg / mL.

[0047] As an example of the present invention, in the modified hole transport layer main material solution, the concentration of the humic acid compound is 0.5 mg / mL.

[0048] In one aspect of the present invention, in the step of preparing a perovskite cell having an inverted structure, the main material of the hole transport layer is selected from any one of NiOx, PTAA, [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphoric acid, [4-(9H-carbazole-9-yl)butyl]phosphoric acid, [2-(9H-carbazole-9-yl)ethyl]phosphoric acid and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).

[0049] In one aspect of the present invention, in the step of preparing a perovskite cell with an inverted structure, the electron transport layer host material is selected from SnO2 or PCBM / BCP.

[0050] In one aspect of the present invention, in the step of preparing a perovskite cell having an upright structure, before step 1-2, a process of subjecting the transparent conductive oxide substrate to an ozone wettability treatment may also be included.

[0051] The beneficial effects of the present invention are:

[0052] The present invention utilizes humic acid compounds, a macromolecular organic substance widely existing in nature, as raw materials to modify the electron transport layer and the hole transport layer at the same time, thereby synergistically changing the interface performance of the perovskite battery. The raw material cost of its preparation process is low and the modification process is simple, which effectively improves the photoelectric conversion efficiency of the perovskite battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is the SEM image of the SnO2 thin film obtained in Example 1.

[0054] Figure 2 This is the SEM image of the SnO2 thin film obtained in Example 4.

[0055] Figure 3 This is the SEM image of the SnO2 thin film obtained in Comparative Example 1. DETAILED DESCRIPTION

[0056] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present application.

[0057] In the present invention, "humic acid" is a natural amorphous macromolecular organic mixture, which is widely present in soil and water. Humic acid substances have different structures, many functional groups, large molecules, and wide distribution, which makes them have rich physical and chemical properties such as solubility, acidity, ion exchange, and complexation.

[0058] In the present invention, the perovskite absorber layer preferably contains a ternary component perovskite, which generally refers to a compound having an ABX3 structure, wherein A and B represent different metal ions or cations, and X represents a non-metallic anion such as oxygen (O), fluorine (F) or chlorine (Cl). In a typical perovskite structure, the A position is usually an alkaline earth metal ion (such as calcium Ca 2+ , Sr 2+ , barium Ba 2+ etc.) or some larger cations (such as rare earth elements), which are located in the cavity formed by the oxygen octahedron; the B position is a transition metal ion (such as titanium Ti 4+ 、Iron 3+ 、Manganese Mn 3+ wait).

[0059] In the present invention, the transparent conductive oxide substrate is preferably conductive glass FTO or ITO.

[0060] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range 3, 4 and 5 are listed, the following ranges can all be expected: 1-2, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0061] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations.

[0062] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0063] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0064] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.

[0065] In the following examples and comparative examples, some of the raw materials used are as follows: SnO2 solution (15wt% aqueous solution), lead iodide (PbI2, 99.9%), and N,N-dimethylformamide (DMF, 99.9%) were purchased from Alfa-Aesar; lead bromide (PbBr2, 99.9%), dimethyl sulfoxide (DMSO, 99.5%), cesium iodide (CsI, 99%), and chlorobenzene (CB, 99.5%) were purchased from Sigma-Aldrich. Methylamine bromide (MABr, 99.9%), formamidine iodine (FAI, 99.9%), Spiro-OMeTAD (i.e. 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene), and 4-tert-butylpyridine (t-BP) were purchased from Xi'an Biolight; sodium humate (97%) and humic acid (90%) were purchased from Titan Reagent Platform. None of the materials used were further processed.

[0066] Example 1

[0067] 1. Preparation of SnO2 electron transport layer modified by sodium humate:

[0068] First, 10 mL of 5 wt% SnO2 aqueous solution was prepared, and then 2 mg of sodium humate was added and stirred at room temperature for 24 hours to obtain a SnO2 solution modified by sodium humate. The modified SnO2 solution was then spin-coated on the conductive glass ITO and calcined at 150°C for 30 minutes to form a SnO2 film; the SnO2 film obtained in Example 1 is as shown in Figure 1 shown.

[0069] 2. Preparation of perovskite film:

[0070] Prepare a 1.4 mol / mL perovskite solution. Weigh 545.4 mg of PbI2, 79.6 mg of PbBr2, 195.0 mg of FAI, 18.1 mg of CsI, and 21.9 mg of MABr and dissolve them in 1 mL of DMF / DMSO (volume ratio 7:3), heat and stir at 60°C for 1 hour, and you have it.

[0071] Then, 30-50 μL of the perovskite solution was spin-coated on the modified SnO2 film substrate, and a toluene anti-solvent process was used to form a corresponding perovskite absorption layer film.

[0072] 3. Preparation of modified Spiro-OMeTAD hole transport layer solution:

[0073] Weigh 5 mg of humic acid and dissolve it in 10 mL of chlorobenzene, stir at room temperature to form a chlorobenzene solution containing humic acid for standby use. Then weigh 72.33 mg of Spiro-OMeTAD and 28.8 μL of t-BP in a reagent bottle, dissolve it in 1 mL of chlorobenzene solution containing humic acid, stir at room temperature for 5 hours, and obtain a modified Spiro-OMeTAD hole transport layer solution.

[0074] 4. Preparation of perovskite devices:

[0075] After the perovskite film prepared above was cooled, the modified Spiro-OMeTAD chlorobenzene solution was spin-coated, and after natural drying, silver electrodes (80 nm thick) were evaporated to assemble into perovskite solar cells. -2 The photoelectric conversion efficiency is tested under standard light. The effective area of ​​the battery is 0.0625cm 2 .

[0076] Example 2

[0077] 1. Preparation of SnO2 electron transport layer:

[0078] First, 10 mL of 5 wt% SnO2 aqueous solution was prepared and stirred at room temperature for 24 hours to obtain a SnO2 solution. The modified SnO2 solution was then spin-coated on the conductive glass ITO and calcined at 150°C for 30 minutes to form a SnO2 film.

[0079] 2. Preparation of perovskite film:

[0080] Prepare a 1.4 mol / mL perovskite solution. Weigh 545.4 mg of PbI2, 79.6 mg of PbBr2, 195.0 mg of FAI, 18.1 mg of CsI, and 21.9 mg of MABr and dissolve them in 1 mL of DMF / DMSO (volume ratio 7:3), heat and stir at 60°C for 1 hour, and you have it.

[0081] Then, 30-50 μL of the perovskite solution was spin-coated on the above SnO2 film substrate, and a toluene anti-solvent process was used to form a corresponding perovskite absorption layer film.

[0082] 3. Preparation of modified Spiro-OMeTAD hole transport layer solution:

[0083] Weigh 5 mg of humic acid and dissolve it in 10 mL of chlorobenzene, stir at room temperature to form a chlorobenzene solution containing humic acid for standby use. Then weigh 72.33 mg of Spiro-OMeTAD and 28.8 μL of t-BP in a reagent bottle, dissolve it in 1 mL of chlorobenzene solution containing humic acid, stir at room temperature for 5 hours, and obtain a modified Spiro-OMeTAD hole transport layer solution.

[0084] 4. Preparation of perovskite devices:

[0085] After the perovskite film prepared above was cooled, it was spin-coated with a modified Spiro-OMeTAD chlorobenzene solution, and after being naturally dried, a silver electrode (80 nm thick) was evaporated to assemble a perovskite solar cell.

[0086] Example 3

[0087] 1. Preparation of SnO2 electron transport layer modified by sodium humate:

[0088] First, 10 mL of 5 wt% SnO2 aqueous solution was prepared, and then 2 mg of sodium humate was added and stirred at room temperature for 24 hours to obtain a sodium humate-modified SnO2 solution. The modified SnO2 solution was then spin-coated on the conductive glass ITO and calcined at 150°C for 30 minutes to form a SnO2 film.

[0089] 2. Preparation of perovskite film:

[0090] Prepare a 1.4 mol / mL perovskite solution. Weigh 545.4 mg of PbI2, 79.6 mg of PbBr2, 195.0 mg of FAI, 18.1 mg of CsI, and 21.9 mg of MABr and dissolve them in 1 mL of DMF / DMSO (volume ratio 7:3), heat and stir at 60°C for 1 hour, and you have it.

[0091] Then, 30-50 μL of the perovskite solution was spin-coated on the modified SnO2 film substrate, and a toluene anti-solvent process was used to form a corresponding perovskite absorption layer film.

[0092] 3. Preparation of Spiro-OMeTAD hole transport layer solution:

[0093] Weigh 72.33 mg of Spiro-OMeTAD and 28.8 μL of t-BP into a reagent bottle and stir at room temperature for 5 h to obtain a Spiro-OMeTAD hole transport layer solution.

[0094] 4. Preparation of perovskite devices:

[0095] After the perovskite film prepared above is cooled, a Spiro-OMeTAD chlorobenzene solution is spin-coated, and after natural drying, a silver electrode (80 nm thick) is evaporated to assemble a perovskite solar cell.

[0096] Example 4

[0097] 1. Preparation of humic acid modified SnO2 electron transport layer:

[0098] First, 10 mL of 5 wt% SnO2 aqueous solution was prepared, and then 2 mg of humic acid was added and stirred at room temperature for 24 hours to obtain a SnO2 solution modified by sodium humate. The modified SnO2 solution was then spin-coated on the conductive glass ITO and calcined at 150°C for 30 minutes to form a SnO2 film; the SnO2 film prepared in Example 4 is as shown in FIG. Figure 2 shown.

[0099] 2. Preparation of perovskite film:

[0100] Prepare a 1.4 mol / mL perovskite solution. Weigh 545.4 mg of PbI2, 79.6 mg of PbBr2, 195.0 mg of FAI, 18.1 mg of CsI, and 21.9 mg of MABr and dissolve them in 1 mL of DMF / DMSO (volume ratio 7:3), heat and stir at 60°C for 1 hour, and you have it.

[0101] Then, 30-50 μL of the perovskite solution was spin-coated on the modified SnO2 film substrate, and a toluene anti-solvent process was used to form a corresponding perovskite absorption layer film.

[0102] 3. Preparation of Spiro-OMeTAD hole transport layer solution:

[0103] Weigh 72.33 mg of Spiro-OMeTAD and 28.8 μL of t-BP into a reagent bottle and stir at room temperature for 5 h to obtain a Spiro-OMeTAD hole transport layer solution.

[0104] 4. Preparation of perovskite devices:

[0105] After the perovskite film prepared above is cooled, a Spiro-OMeTAD chlorobenzene solution is spin-coated, and after being naturally dried, a silver electrode (80 nm thick) is evaporated to assemble a perovskite solar cell.

[0106] Comparative Example 1

[0107] 1. Preparation of SnO2 electron transport layer:

[0108] First, 10 mL of 5 wt% SnO2 aqueous solution was prepared to obtain a SnO2 solution. The SnO2 solution was then spin-coated on the conductive glass ITO and calcined at 150°C for 30 min to form a SnO2 film. The SnO2 film prepared in Comparative Example 1 was as follows: Figure 3 shown.

[0109] 2. Preparation of perovskite film:

[0110] Prepare a perovskite solution with a concentration of 1.4 mol / mL. Weigh 545.4 mg of PbI2, 79.6 mg of PbBr2, 195.0 mg of FAI and 18.1 mg of CsI, and 21.9 mg of MABr and dissolve them in 1 mL of DMF / DMSO (volume ratio 7:3), heat and stir at 60°C for 1 h, and you have it.

[0111] Then, 30-50 μL of the perovskite solution was spin-coated on the above SnO2 film substrate, and a toluene anti-solvent process was used to form a corresponding perovskite absorption layer film.

[0112] 3. Preparation of Spiro-OMeTAD hole transport layer solution:

[0113] Weigh 72.33 mg of Spiro-OMeTAD and 28.8 μL of t-BP into a reagent bottle and stir at room temperature for 5 h to obtain a Spiro-OMeTAD hole transport layer solution.

[0114] 4. Preparation of perovskite devices:

[0115] After the perovskite film prepared above is cooled, a Spiro-OMeTAD chlorobenzene solution is spin-coated, and after being naturally dried, a silver electrode (80 nm thick) is evaporated to assemble a perovskite solar cell.

[0116] Experimental Example 1

[0117] Photoelectric conversion efficiency test.

[0118] Through the solar simulator, at 100mW cm -2 Under the irradiation of standard light, the photoelectric conversion efficiency of Examples 1-4 and Comparative Example 1 was tested, and the results are shown in Table 1.

[0119] Table 1

[0120] Example <![CDATA[Current density (mA cm -2 )]]> Open circuit voltage(V) Fill factor (%) Photoelectric conversion efficiency (%) Example 1 25.34 1.14 83.7 24.17 Example 2 25.32 1.11 81.7 22.96 Example 3 25.52 1.13 82.6 23.81 Example 4 25.34 1.12 83.1 23.58 Comparative Example 1 25.12 1.12 77.9 21.13

[0121] It can be seen that compared with Comparative Example 1, the photoelectric conversion efficiency of the SnO2-based battery modified by humic acid or sodium humate is greatly improved, among which the battery efficiency is the highest when sodium humate and humic acid are used to modify the d electron transport layer and the hole transport layer respectively.

[0122] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A perovskite battery, characterized in that: The perovskite battery comprises an electron transport layer and a hole transport layer, wherein the electron transport layer comprises an electron transport layer main material modified by a humic acid compound, and the hole transport layer comprises a hole transport layer main material modified by a humic acid compound.

2. The perovskite battery according to claim 1, characterized in that: The electron transport layer is obtained by solidifying a modified electron transport layer main material solution, and the modified electron transport layer main material solution is obtained by the following steps: providing a solution containing an electron transport layer host material; The solution containing the electron transport layer main material is doped and modified by using a humic acid compound to obtain a modified electron transport layer main material solution.

3. The perovskite battery according to claim 1, characterized in that: The hole transport layer is obtained by solidifying the modified hole transport layer main material solution, and the modified hole transport layer main material solution is obtained by the following steps: providing a solution comprising a hole transport layer host material; The solution containing the hole transport layer main material is modified by using the humic acid compound to obtain a modified hole transport layer main material solution.

4. The perovskite battery according to any one of claims 1 to 3, characterized in that: The humic acid compound is selected from at least one of humic acid, humate, fulvic acid, humic acid ester, humic acid aldehyde, humic acid amide and humic acid.

5. The perovskite battery according to any one of claims 1 to 3, characterized in that: The perovskite cell satisfies at least one of the following conditions: (1) In the modified electron transport layer main material solution, the concentration of the humic acid compound is 0.001-2 mg / mL; (2) In the modified hole transport layer main material solution, the concentration of the humic acid compound is 0.001-5 mg / mL; (3) The main material of the hole transport layer is selected from any one of NiOx, 2,2',7,7'-tetrabromo-9,9'-spirobifluorene, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene and tri(4-iodophenyl)amine; (4) The main material of the electron transport layer is selected from SnO2.

6. A method for preparing a perovskite battery according to any one of claims 1 to 5, characterized in that: The perovskite cell has an upright structure, and is provided with a transparent conductive oxide substrate, an electron transport layer, a perovskite absorption layer, a hole transport layer and a metal electrode in sequence from bottom to top; the method comprises the following steps: Step 1-1: preparing an electron transport layer main material solution modified by a humic acid compound and coating the modified electron transport layer main material solution on the transparent conductive oxide substrate, and obtaining an electron transport layer after curing; Step 2-1: coating a perovskite absorption layer on the electron transport layer to form a perovskite absorption layer; Step 3-1: coating a hole transport layer main material solution modified by a humic acid compound on a surface of the perovskite absorption layer away from the electron transport layer, and obtaining a hole transport layer after curing; Step 4-1: Perform the process of evaporating electrodes and, after subsequent assembly steps, obtain a perovskite cell with an upright structure.

7. The method according to claim 6, characterized in that Between step 1-1 and step 2-1, it also includes a process of subjecting the electron transport layer to an ozone wettability treatment, wherein the ozone wettability treatment is to place the electron transport layer in an ozone cleaning machine and perform surface ozone cleaning, and the cleaning time is selected from 15-30 minutes.

8. The method according to claim 6, characterized in that The method satisfies at least one of the following conditions: (1) In step 1-1, the coating method is selected from spin coating, scraper coating, spray coating or drop coating; (2) In step 3-1, the curing method is low-temperature calcination annealing at 150°C-180°C.

9. A method for preparing a perovskite battery according to any one of claims 1 to 5, characterized in that: The perovskite cell has an inverted structure, and is provided with a transparent conductive oxide substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and a metal electrode in sequence from bottom to top. The method comprises the following steps: Step 1-2: preparing a hole transport layer main material solution modified by a humic acid compound and coating the modified hole transport layer main material solution on the transparent conductive oxide substrate, and obtaining a hole transport layer after curing; Step 2-2: coating a perovskite absorption layer on the hole transport layer to form a perovskite absorption layer; Step 3-2: coating a solution of an electron transport layer main material modified by a humic acid compound on a surface of the perovskite absorption layer away from the hole transport layer, and obtaining an electron transport layer after curing; Step 4-2: Perform the process of evaporating electrodes and, after subsequent assembly steps, obtain a perovskite cell with an inverted structure.

10. The method according to claim 9, characterized in that The method satisfies at least one of the following conditions: (1) In the modified electron transport layer main material solution, the concentration of the humic acid compound is selected from 0.001-2 mg / mL; (2) In the modified hole transport layer main material solution, the concentration of the humic acid compound is selected from 0.001-5 mg / mL; (3) The main material of the hole transport layer is selected from any one of NiOx, PTAA, [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphoric acid, [4-(9H-carbazole-9-yl)butyl]phosphoric acid, [2-(9H-carbazole-9-yl)ethyl]phosphoric acid and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene; (4) The main material of the electron transport layer is SnO2 or PCBM / BCP.

Citation Information

Patent Citations

  • Ternary organic wide-spectrum photoelectric detector and manufacturing method thereof

    CN110473971A

  • Preparation method and application of dual-heterojunction passivated perovskite cell interface

    CN116390503A

  • Perovskite solar cell module and preparation method thereof

    CN118317665A